Preventive Solutions for Racial Conflict from the Perspective of the Qur'an - Iwan Satiri; Muhammad Hariyadi (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2024)
Racial conflict is a clash between different racial groups due to clashing interests and cultures. Racial conflict generally occurs because one race feels superior and more perfect than the others. This paper is based on the theory of intercultural misunderstanding and public relations theory. The theory of intercultural misunderstanding states that conflict occurs due to incompatibility in communication methods between different cultures. Public relations theory states that conflict occurs due to mistrust between different groups. This study reveals several preventive solutions for racial conflict from a Qur'anic perspective: eliminating primordial attitudes, eliminating racist attitudes, and eliminating stereotypical attitudes.